Analyzing the adaptability of MoWebA to different environments - T., Magalí González; Cernuzzi, Luca (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de Software, 2024)
Some of the major challenges facing Web applications are those of portability, adaptability, and evolution, not only in the environment in which they run but also in the way in which they must be developed, often requiring different languages, frameworks, tools, environments, platforms, etc. MDD takes into account these issues. However, achieving portability, adaptability, and evolution depends to some extent on the degree of independence that the models adopt. This paper focuses on the Architecture Specific Model (ASM) of MoWebA (Model Oriented Web Approach). It analyses its impact on portability and adaptability across different architectures. A case study is presented to validate this issue by extending MoWebA to three different architectures. In such extensions, we analyze the grade of adaptability of MoWebA and automation of PIM-ASM, as well as the grade of independence of the PIM metamodel.